QcrC is a potential target for antibody therapy and vaccination to control Campylobacter jejuni infection by suppressing its energy metabolism - Hosomi, Koji; Hatanaka, Noritoshi; Hinenoya, Atsushi; Adachi, Jun; Tojima, Yoko; Furuta, Mari; Uchiyama, Keita; Morita, Makiko; Nagatake, Takahiro; Saika, Azusa; Kawai, Soichiro; Yoshii, Ken; et al. (Frontiers in Microbiology, 2024)
Campylobacter spp. are a public health concern, yet there is still no effective vaccine or medicine available. Here, we developed a Campylobacter jejuni-specific antibody and found that it targeted a menaquinol cytochrome c reductase complex QcrC. The antibody was specifically reactive to multiple C. jejuni strains including clinical isolates from patients with acute enteritis and was found to inhibit the energy metabolism and growth of C. jejuni. Different culture conditions produced different expression levels of QcrC in C. jejuni, and these levels were closely related not only to the energy metabolism of C. jejuni but also its pathogenicity. Furthermore, immunization of mice with recombinant QcrC induced protective immunity against C. jejuni infection. Taken together, our present findings highlight a possible antibody-or vaccination-based strategy to prevent or control Campylobacter infection by targeting the QcrC-mediated metabolic pathway.